The Analysis of Copra Farming Revenue and Factors Influencing it in Palam Village Subdistrict of North Tinangkung, District of Banggai Kepulauan - Mohammad Ikhsan Diman; Rustam Abdul Rauf; Yulianti Kalaba (AGROLAND The Agricultural Sciences Journal (e-Journal), 2016)
Coconut is one of the export commodities of sub sector farm which is best commodity of Central Sulawesi Province. This research aims to: (1) analize the income of copra farm in Palam Village of North Tinangkung District of Banggai Kepulauan Regency and (2) Analyze the factoedrs affect copra farm in Palam Villageof North Tinangkung District of Banggai Kepulauan Regency. The method usedwas survey and sample was selected using simple random. The number of the sample was 40 households. The research results indicate that.: (1) avarege of totalcost of copra farm was Rp 14.648.819.85/ 10.003/coconut/1 time production. The aferage of acceptance of copra farm was Rp 20.502.768.75/1 time production with the average of sell price Rp 9.093.75/kg, so, the average income of copra farm was Rp 5.853.948.90/10.003 coconut/1 time production and (2) F counted = 32.163 with probability ρ =0.000 < 0.05 at α =5% proving that Null Hypothesis is rejected which means independent variable of self price (X1), production cost (X2) and copra production (X3) simultaneusly affect copra farm income in Palam Village of Nort Tinangkung District of Banggai Kepulauan Regency determinant (R2) adjusted was 0.728 showing that income variation on copra farm (Y) can be explained by independent variable of sell price (X1), production cost (X2), and copra production (X3) was 72.8%, whereas 27.2% explained by other factor excluded of the model. Partially the price sell and copra production positively affect and significant on copra farm income while production cost negatifely affect on confidence level of 95%.